SAS coding primer and reference guide - Tang, Connie Kelly (Boca Raton, FL : CRC Press, 2020)
Although the web and online SAS communities can provide volumes of information for programmers, these resources are often overwhelming and lack a simple path to guide coding SAS. This reference, however, does provide such a path from a data user's standpoint vs. seeing things as a code writer. Written by an experienced SAS programmer, this book lets SAS coders easily find explanations and clarification to typical programming problems. This book presents practical real-world data analysis steps encountered by analysts in the field. These steps include the following: Getting to know raw data Understanding variables Getting data into SAS Creating new data variables Performing data manipulations, including sorting, ranking, grouping, subtotal, total, and percentage Statistical testing under a broad range of logical and conditional settings Data visualization Throughout this book, statements and codes are accompanied by thorough annotation. Line-by-line explanations ensure that all terms are clearly explained. Code examples and sample codes have broad usages. All the examples are related to highway transportation where the use of big data is exploding and presenting new challenges and opportunities for growth. Clear and precise practical introductory material on statistics is integrated into the relevant SAS procedures to bolster users' confidence in applying such methods to their own work. Comprehensive and foundational coverage, systematic introduction of programming topics, thoroughly annotated code examples, and real-world code samples combine to make SAS Coding Primer and Reference Guide an indispensable reference for beginners and experienced programmers.
OCLC-licensed vendor bibliographic record.
Keywords: Coding theory; Computer programming; SAS (Computer program language); COMPUTERS / Database Management / General; COMPUTERS / Database Management / Data Mining; COMPUTERS / Information Technology